Histone Deacetylase 1 and Sirtuin 1 Expression in Psoriatic Skin: A Comparison between Guttate and Plaque Psoriasis - Young-Ji Hwang; Jung-Im Na; Sang-Young Byun; Soon-Hyo Kwon; Seung-Hye Yang; Hyun-Sun Lee; Hye-Ryung Choi; Soyun Cho; Sang Woong Youn; Kyoung-Chan Park (Life, 2020)
Abnormal histone modification by histone deacetylases (HDACs), including HDAC1 and sirtuin 1 (SIRT1), has been reported to play an important role in the pathogenesis of psoriasis by altering cell proliferation, differentiation, and inflammation. However, findings on the expression level of HDACs in psoriatic skin lack consistency. We assessed the expression of HDAC1, SIRT1, p63, and proliferating cell nuclear antigen (PCNA) in skin tissues from 23 patients with psoriasis (15 with plaque psoriasis and eight with guttate psoriasis) and five healthy individuals using immunohistochemistry, and analyzed their associations with clinical phenotypes of the disease. The expression of HDAC1 and keratinocyte proliferative markers, such as p63 and PCNA significantly increased, whereas that of SIRT1 decreased in the basal layer (p < 0.05) of the patients with psoriasis compared to those in healthy controls. Among the patients with psoriasis, expression of HDAC1, p63, and PCNA was significantly higher in plaque psoriasis than in guttate psoriasis. There was no significant differences in the level of SIRT1 between the two clinical phenotypes. The findings of this study suggest that histone modifications are involved in the pathogenesis of psoriasis and may contribute to the formation of clinical phenotypes.